Pyrotinib with trastuzumab and aromatase inhibitors as first-line treatment for HER2 positive and hormone receptor positive metastatic or locally advanced breast cancer: study protocol of a randomized controlled trial - Changjun Wang; Yan Lin; Yidong Zhou; Feng Mao; Hanjiang Zhu; Jinghong Guan; Xiaohui Zhang; Songjie Shen; Xin Huang; Chang Chen; Ru Yao; Jialin Zhao; et al. (BMC Cancer, 2020)
Abstract Background HER2 dual-blockade combined with aromatase inhibitors (AI) is a promising strategy to improve progression-free survival (PFS) in hormone receptor (HR) positive, metastatic breast cancer (MBC). Pyrotinib is a novel irreversible epidermal growth factor receptor/HER2 dual tyrosine kinase inhibitor. However, there is scarcity of data on the effectiveness and safety of pyrotinib combined with trastuzumab and AI as first-line treatment in a metastatic setting. Methods/design The present study is a prospective, randomized, open-label trial. 198 patients with HER2+/HR+ MBC will be recruited. Eligible patients will be allocated (2:1) to either an experimental group (pyrotinib + trastuzumab + AI) or a control group (trastuzumab + AI). Allocation will be stratified by 1) time since adjuvant hormone therapy (≤ 12 months/> 12 months/no prior hormone therapy); 2) lesion sites (visceral / non-visceral). The primary endpoint is PFS. Discussion To our knowledge, this is the first prospective randomized controlled trial to assess dual HER2-blockade with pyrotinib in the metastatic setting. This study will provide valuable evidence regarding the efficacy and safety of pyrotinib when combined with trastuzumab and an AI as first-line treatment for MBC. Moreover, it will also evaluate the feasibility of endocrine therapy as an alternative to chemotherapy in providing de-escalation therapy with less toxicity for advanced HR+/HER2+ patients. Trial registration ClinicalTrials.gov, ID: NCT03910712 . Registered on 10 Apr. 2019.